Modelling energy expenditure of a brick layer at various postures (2008)
Energy utilisation at work in the labour-intensive building industry is of prime importance to contractors who match people to jobs. This paper provides an insight into modelling energy expenditure in a specific task, namely brick laying in various postures. It therefore takes previous "generic" biomechanical-energy prediction models, and makes the case for applying and adapting broader theoretical models to a specific occupational task. This refinement of established models provides a meaningful and valuable contribution to interpreting and predicting energy expenditure during a defined occupational task -- brick laying. Results obtained show that in the standing position, fewer muscles are brought into action. For the sitting position, the muscles are more relaxed, relieving the bricklayer of stress, but the center of gravity is still lower than the standing position. In the case of squatting, there is a lot of strain in the body by considering the muscles of the arms, legs, and back resulting in more energy released in the body. The bending position has repeated movement of the muscles at the back and the center of gravity varies. Thus, this research of energy expenditure in brick layers may be of interest to ergonomists and those interested in biomechanical-energy modelling.